A Real-Business-Cycle model with efficiency wages and fiscal policy: the case of Bulgaria - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we investigate the quantitative importance of efficiency wages in explaining fluctuations in Bulgarian labor markets. This is done by augmenting an otherwise standard real business cycle model a la Long and Plosser (1983) with unobservable workers effort by employers and wage contracts as in Shapiro and Stiglitz (1984). This imperfection in labor markets introduces a strong propagation mechanism that allows the model to capture the business cycles in Bulgaria better than earlier models. The model performs well vis-a-vis data, especially along the labor market dimension, and in addition dominates the market-clearing labor market framework featured in the standard RBC model, e.g Vasilev (2009).
Keywords: E24; E32; 330; general equilibrium; shirking; efficiciency wages; unemployment